Physical attractiveness and women’s intra-household bargaining power - Li, Zhongwu (Frontiers in Psychology, 2022)
This paper explores the role of physical attractiveness in affecting women’s intrahousehold bargaining power. The empirical analysis based on the China Family Panel Studies finds that physical attractiveness significantly increases women’s intrahousehold bargaining power. To solve the endogenous problem of physical attractiveness, we employ an instrument variable-based regression to corroborate the conclusion. Using generalized structural equation model, we show that income, self-esteem, and interpersonal relationship are three possible transmission channels (or mediators) between physical attractiveness and women’s intrahousehold bargaining power.